IMPLEMENTING MODELLING TRANSPORTATION DUE TO LAMPUNG'S ECONOMIC MASTER PLAN - Sulistyorini, Rahayu (FSTPT Indonesia, 2015)
Rapid economic growth in Lampung needs support from adequate transport facility and development of the infrastructure project is a solution. This research aims to model the travel pattern based on potential economic due to the sunda strait bridge development plan to support KSN Sunda Strait and Economic Corridors in Lampung. Road network modeling formed for assignment stage, being utilized to predict road traffic in the future. Assignmet process using SATURN as transportation software. The scenario is a road performance analysis after 10 (ten) years using traffic growth and several assumption such as Bakauheni – Babatan – Tegineneng toll road , have functioned and can be used; Sunda Strait Bridge constructed and can be used. The bridge project would help boost the growth of strategic economic area. In order to boost economic development in Sumatera and especially Lampung , the government already has program to build toll roads. Various constraints, such as the preparation of project implementation, land as well as financing, have become barriers that make it difficult for those projects to commence in the planned.